A robust culture system to generate neural progenitors with gliogenic competence from clinically relevant induced pluripotent stem cells for treatment of spinal cord injury. (23rd November 2020) - Kamata, Yasuhiro; Isoda, Miho; Sanosaka, Tsukasa; Shibata, Reo; Ito, Shuhei; Okubo, Toshiki; Shinozaki, Munehisa; Inoue, Mitsuhiro; Koya, Ikuko; Shibata, Shinsuke; Shindo, Tomoko; Matsumoto, Morio; et al.
Abstract: Cell-based therapy targeting spinal cord injury (SCI) is an attractive approach to promote functional recovery by replacing damaged tissue. We and other groups have reported the effectiveness of transplanting neural stem/progenitor cells (NS/PCs) derived from human induced pluripotent stem cells (hiPSCs) in SCI animal models for neuronal replacement. Glial replacement is an additional approach for tissue repair; however, the lack of robust procedures to drive iPSCs into NS/PCs which can produce glial cells has hindered the development of glial cell transplantation for the restoration of neuronal functions after SCI. Here, we established a method to generate NS/PCs with gliogenic competence (gNS/PCs) optimized for clinical relevance and utilized them as a source of therapeutic NS/PCs for SCI. We could successfully generate gNS/PCs from clinically relevant hiPSCs, which efficiently produced astrocytes and oligodendrocytes in vitro. We also performed comparison between gNS/PCs and neurogenic NS/PCs based on single cell RNA-seq analysis and found that gNS/PCs were distinguished by expression of several transcription factors including HEY2 and NFIB . After gNS/PC transplantation, the graft did not exhibit tumor-like tissue formation, indicating the safety of them as a source of cell therapy. Importantly, the gNS/PCs triggered functional recovery in an SCI animal model, with remyelination of demyelinated axons and improved motor function. Given the inherent safety of gNS/PCs and favorable outcomes observed after their transplantation, cell-based medicine using the gNS/PCs-induction procedure described here together with clinically relevant iPSCs is realistic and would be beneficial for SCI patients. Abstract : Our study demonstrated a successful and robust procedure to generate neural stem progenitor cells (NS/PCs) with gliogenic competence from clinically relevant induced pluripotent stem cells, which in turn efficiently differentiated into astrocytes and oligodendrocytes in vitro and in vivo. These findings indicate that our method to produce gliogenic NS/PCs will be useful for developing cell-based therapies for spinal cord injury.